The Role of Artificial Intelligence in Transforming Smart Tourism: Enhancing Customer Experience and Service Personalization - Sidiq, Zaini Fajar; Z, Sahman; Wahyuzi, Zikri; Ifada, Zuriyat (Universitas Muhammadiyah Mataram, 2025)
Abstract: This research aims to examine the role of artificial intelligence (AI) in transforming smart tourism, with a focus on improving traveler experience and personalizing services. A Systematic Literature Review approach was used to analyze literature published in the last 10 years from reputable indexers such as Dimensions, DOAJ and Scopus. The results show that technologies such as AI, virtual reality (VR), and augmented reality (AR) have great potential to revolutionize the tourism industry. These technologies enable personalization of services, more efficient management of tourist flows, as well as the provision of real-time relevant information that can improve tourist experience and environmental sustainability. Despite progress in the application of these technologies, research gaps still exist, particularly in developing smart tourism models that integrate local and cultural values, as well as the application of technologies that support ecosystem preservation. In Indonesia, the development of smart tourism models that take into account the richness of local culture and history needs to be further encouraged through further research to create an inclusive and sustainable approach. Therefore, there is a need to develop a smart tourism model that integrates ecosystem sustainability, cultural heritage preservation, and technological solutions to address ethical issues related to the use of travelers' personal data.Abstrak: Penelitian ini bertujuan untuk mengkaji peran kecerdasan buatan (AI) dalam mentransformasi pariwisata cerdas, dengan fokus pada peningkatan pengalaman wisatawan dan personalisasi layanan. Pendekatan Systematic Literature Review digunakan untuk menganalisis literatur yang dipublikasikan dalam 10 tahun terakhir dari pengindeks bereputasi seperti Dimensions, DOAJ dan Scopus. Hasil penelitian menunjukkan bahwa teknologi seperti AI, realitas virtual (VR), dan augmented reality (AR) memiliki potensi besar untuk merevolusi industri pariwisata. Teknologi ini memungkinkan personalisasi layanan, pengelolaan aliran wisatawan yang lebih efisien, serta penyediaan informasi relevan secara real-time yang dapat meningkatkan pengalaman wisatawan dan keberlanjutan lingkungan. Meskipun ada kemajuan dalam penerapan teknologi ini, kesenjangan riset masih ada, khususnya dalam mengembangkan model pariwisata cerdas yang mengintegrasikan nilai lokal dan budaya, serta penerapan teknologi yang mendukung pelestarian ekosistem. Di Indonesia, pengembangan model pariwisata cerdas yang memperhitungkan kekayaan budaya dan sejarah lokal perlu lebih didorong melalui riset lebih lanjut untuk menciptakan pendekatan yang inklusif dan berkelanjutan. Oleh karena itu, perlu ada pengembangan model pariwisata cerdas yang mengintegrasikan keberlanjutan ekosistem, pelestarian warisan budaya, dan solusi teknologi untuk mengatasi masalah etika terkait penggunaan data pribadi wisatawan.